Binding of mismatch repair protein MutS to mispaired DNA adducts of intercalating ruthenium(II) arene complexes - Castellano-Castillo, Maria; Kostrhunova, Hana; Marini, Victoria; Kasparkova, Jana; Sadler, Peter J; Malinge, Jean-Marc; Brabec, Viktor (Journal of biological inorganic chemistry, 2008)
The present study was performed to examine the affinity of Escherichia coli mismatch repair (MMR) protein MutS for DNA damaged by an intercalating compound. We examined the binding properties of this protein with various DNA substrates containing a single centrally located adduct of ruthenium(II) arene complexes [(eta(6)-arene)Ru(II)(en)Cl][PF(6)] [arene is tetrahydroanthracene (THA) or p-cymene (CYM); en is ethylenediamine]. These two complexes were chosen as representatives of two different classes of monofunctional ruthenium(II) arene compounds which differ in DNA-binding modes: one that involves combined coordination to G N7 along with noncovalent, hydrophobic interactions, such as partial arene intercalation (tricyclic-ring Ru-THA), and the other that binds to DNA only via coordination to G N7 and does not interact with double-helical DNA by intercalation (monoring Ru-CYM). Using electrophoretic mobility shift assays, we examined the binding properties of MutS protein with various DNA duplexes (homoduplexes or mismatched duplexes) containing a single centrally located adduct of ruthenium(II) arene compounds. We have shown that presence of the ruthenium(II) arene adducts decreases the affinity of MutS for ruthenated DNA duplexes that either have a regular sequence or contain a mismatch and that intercalation of the arene contributes considerably to this inhibitory effect. Since MutS initiates MMR by recognizing DNA lesions, the results of the present work support the view that DNA damage due to intercalation is removed from DNA by a mechanism(s) other than MMR.
Keywords: Ruthenium; interkalátory; Protein Binding; poškození DNA; sekvence nukleotidů; adukty DNA; anthraceny; vazebná místa; DNA Damage; Structure-Activity Relationship; cymeny; molekulární struktura; Molecular Structure; Escherichia coli; monoterpeny; ethylendiaminy; Monoterpenes; chybné párování bází; Organometallic Compounds; vztahy mezi strukturou a aktivitou; ruthenium; vazba proteinů; Binding Sites; vazebný protein MutS opravné syntézy DNA; Anthracenes; DNA Adducts; Cymenes; Intercalating Agents; DNA; Base Sequence; Base Pair Mismatch; Ethylenediamines; organokovové sloučeniny; MutS DNA Mismatch-Binding Protein